Potential Activities and Long Lifetimes of Organic Carbon-Degrading Extracellular Enzymes in Deep Subsurface Sediments of the Baltic Sea - Schmidt, Jenna M.; Royalty, Taylor M.; Lloyd, Karen G.; Steen, Andrew D. (Frontiers in Microbiology, 2021)
Heterotrophic microorganisms in marine sediments produce extracellular enzymes to hydrolyze organic macromolecules so their products can be transported inside the cell and used for energy and growth. Therefore, extracellular enzymes may mediate the fate of organic carbon in sediments. The Baltic Sea Basin is a primarily depositional environment with high potential for organic matter preservation. The potential activities of multiple organic carbon-degrading enzymes were measured in samples obtained by the International Ocean Discovery Program (IODP) Expedition 347 from the Lillebælt Strait, Denmark, core M0059C. Potential maximum hydrolysis rates (Vmax) were measured at depths down to 77.9 mbsf for the following enzymes: alkaline phosphatase, β-d-xylosidase, β-d-cellobiohydrolase, N-acetyl- β-d- glucosaminidase, β-glucosidase, α-glucosidase, leucyl aminopeptidase, arginyl aminopeptidase, prolyl aminopeptidase, gingipain, and clostripain. Extracellular peptidase activities were detectable at depths shallower than 54.95 mbsf and alkaline phosphatase activity was detectable throughout the core, albeit against a relatively high activity in autoclaved sediments. β-glucosidase activities were detected above 30 mbsf, however activities of other glycosyl hydrolases (β-xylosidase, β- cellobiohydrolase, N-acetyl-β- glucosaminidase and α-glucosidase) were generally indistinguishable from zero at all depths. These extracellular enzymes appear to be extremely stable: among all enzymes, a median of 51.3% of enzyme activity was retained after autoclaving for an hour. We show that enzyme turnover times scale with the inverse of community metabolic rates, such that enzyme lifetimes in subsurface sediments, in which metabolic rates are very slow, are likely to be extraordinarily long. A back-of-the-envelope calculation suggests enzyme lifetimes are, at minimum, on the order of hundreds to thousands of hours, and may be substantially longer. These results lend empirical support to the hypothesis that a population of subsurface microbes persist by using extracellular enzymes to slowly metabolize old, highly degraded organic carbon.